If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + -16 = 18x + 6 Reorder the terms: -16 + 20x = 18x + 6 Reorder the terms: -16 + 20x = 6 + 18x Solving -16 + 20x = 6 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. -16 + 20x + -18x = 6 + 18x + -18x Combine like terms: 20x + -18x = 2x -16 + 2x = 6 + 18x + -18x Combine like terms: 18x + -18x = 0 -16 + 2x = 6 + 0 -16 + 2x = 6 Add '16' to each side of the equation. -16 + 16 + 2x = 6 + 16 Combine like terms: -16 + 16 = 0 0 + 2x = 6 + 16 2x = 6 + 16 Combine like terms: 6 + 16 = 22 2x = 22 Divide each side by '2'. x = 11 Simplifying x = 11
| -(13+g)=-9 | | 61+4y-28=15y-9-4y | | 80=91x | | 2.9y+1.7=3.5+23y | | -2(-3x-1)-3=-4 | | 9y-9=7y+1 | | x+18+4x=-48-4x-51 | | 4(7x+5)-48x=10x-10 | | 9p+8q=108 | | 6x-12=4(x+7) | | 2cos^2(x)-4cos(x)=0 | | (9x^2-7)*(9x^2+7)= | | 2/9-3 | | 8P+4Q=68 | | x^2+ln(-x+4)= | | 2(x+5)=8is | | 25s^2-81=0 | | 13=5-13+3c | | 2x+-5y+9=0 | | 13=5+4a | | 7428=p*6 | | 13-5=4a | | f(x)=-120+5x | | g+g+g=(1+g) | | 1-12=z/-4 | | -15x+25=220 | | 9t^2-20t-21=0 | | kx^2+3x-k+5=0 | | x^2+2xy=8 | | x-7=-2+5 | | (a^2-1/2*a)^5 | | -5+6=4+x |